A linear system is a collection of equations of multiple (at least 2) unknowns similar to the equations you have shown. Each term contains a maximum of one unknown to the first degree.
Read up
http://en.wikipedia.org/wiki/Simultaneous_equations
for more information, and also the method of elimination.
If you could post your attempt at the solution, I will be pleased to look over the solution with you.
What is the linear system?
2x+2y=16
4x-6y=2
I am using elimination to solve
Please help!
3 answers
thank you, but I already know how to solve it, the problem I am having is with this certain problem because the y values are not the same, I am not sure what to do because of this
Thanks, it's much easier when you pin-point the problem!
In general, the coefficients of x and y are not the same between the two equations.
When you want to eliminate y, and the coefficients are not the same, you find the LCM (lowest common multiple) of the two coefficients and multiply each equation by the LCM/divided by the coefficient, then both coefficients will end up being the LCM.
Fist, you check if there are common factors in each equation. If there are, divide the whole equation by the common factor to reduce the equations to the lowest terms. It is not necessary, but will make your life easier.
2x+2y=16 => x+y=8
4x-6y=2 => 2x-3y=1
The LCM between the coefficients of y (1 and -3) being 3, the second equation will not change. We multiply the first equation by 3 to get
3x+3y=24
2x-3y=1
Can you take it from her now?
In general, the coefficients of x and y are not the same between the two equations.
When you want to eliminate y, and the coefficients are not the same, you find the LCM (lowest common multiple) of the two coefficients and multiply each equation by the LCM/divided by the coefficient, then both coefficients will end up being the LCM.
Fist, you check if there are common factors in each equation. If there are, divide the whole equation by the common factor to reduce the equations to the lowest terms. It is not necessary, but will make your life easier.
2x+2y=16 => x+y=8
4x-6y=2 => 2x-3y=1
The LCM between the coefficients of y (1 and -3) being 3, the second equation will not change. We multiply the first equation by 3 to get
3x+3y=24
2x-3y=1
Can you take it from her now?